2017
DOI: 10.21608/ejar.2017.146862
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological and Molecular Detection of Theileria Equi in Donkeys in Assiut Governorate

Abstract: heileria equi is a tick-borne hemoprotozoan parasite and one of the causative agents of equine piroplasmosis. Data on T. equi infection in donkeys are scarce in Assiut governorate, Egypt. This study was conducted on the prevalence of T. equi infection in donkeys by using micropscopic examination and polymerase chain reaction (PCR) assay. Out of 50 donkeys, blood samples examined for T. equi, 14% (7/50) were positive by microscopic examination and 38% (19/50) by PCR. Prevalence of T. equi had high significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…equi was investigated in clinically ill and apparently healthy horses reared in Dakahlia province, Egypt. Microscopically, the identified piroplasm of T. equi were similar to that reported previously(OIE, 2008;Kuraa and Nageib, 2017;Soliman et al 2021) Nested PCR assay revealed presence of the infection in 14-animals. While only 9 horses appeared positive during microscopic examination of blood smears.…”
supporting
confidence: 87%
“…equi was investigated in clinically ill and apparently healthy horses reared in Dakahlia province, Egypt. Microscopically, the identified piroplasm of T. equi were similar to that reported previously(OIE, 2008;Kuraa and Nageib, 2017;Soliman et al 2021) Nested PCR assay revealed presence of the infection in 14-animals. While only 9 horses appeared positive during microscopic examination of blood smears.…”
supporting
confidence: 87%